2017
DOI: 10.1186/s12978-017-0291-8
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ views about sexual health education for their adolescent daughters: a qualitative study

Abstract: BackgroundGiven that mothers play a role in the sexual education of their daughters, it is important to understand their views of sexual health and related programs. This study was aimed at exploring mothers’ perspectives regarding sexual health education for their adolescent daughters in Mahshahr, Iran.MethodsIn this qualitative study, in-depth interviews with ten key informants and five focus group discussions involving 28 mothers with daughters aged 12–18 were conducted. All the discussions were audio-recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…Parents' perception significantly influenced communication on adolescents' sexual health. This is in agreement with Shams, Parhikar, S, Mousavizadeh, & Majdpour, [8] and Mathew, Shugaba and Ogala [9] who revealed that parent-child communication on sexual matters was attributed to the perception of parents on sexual health. This finding indicates the relevance of the Theory of Planned Behaviour by Ajzen [10], which posited that belief plays a central role in human behaviour, especially those salient behavioural beliefs that are most readily accessible in memory.…”
Section: Discussionsupporting
confidence: 89%
“…Parents' perception significantly influenced communication on adolescents' sexual health. This is in agreement with Shams, Parhikar, S, Mousavizadeh, & Majdpour, [8] and Mathew, Shugaba and Ogala [9] who revealed that parent-child communication on sexual matters was attributed to the perception of parents on sexual health. This finding indicates the relevance of the Theory of Planned Behaviour by Ajzen [10], which posited that belief plays a central role in human behaviour, especially those salient behavioural beliefs that are most readily accessible in memory.…”
Section: Discussionsupporting
confidence: 89%
“…This can show that families are more careful about the behaviors of their children, especially girls but after they enter a university this surveillance will decrease (27). Sexual health education for daughters should be initiated by mothers but fears about stimulating the curiosity of adolescent and temptation to engage in sexual relation, insufficient knowledge of parents about sexual and inability of mothers in communication, are barriers to education (28). Contrary to parents' concern about youth's sexual knowledge, sexual awareness and education can reduce sexual behaviors (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Fear of encouraging children to begin sexual activity also stood out in a recent study performed with mothers of adolescent girls in Australia. 19 In the present study, some of the participants reported that they believed adolescents approaching themes related to sexual health could be a facilitator of experimentation of risk sexual behavior. 19 Adolescents mentioned some family members such as uncles/aunts and siblings as sources to answer questions about sexuality.…”
Section: My Mom Is Not Open To Talk About This I've Tried Before Onmentioning
confidence: 96%
“…19 In the present study, some of the participants reported that they believed adolescents approaching themes related to sexual health could be a facilitator of experimentation of risk sexual behavior. 19 Adolescents mentioned some family members such as uncles/aunts and siblings as sources to answer questions about sexuality. According to adolescents, conversation flows better with these family members, compared to parents or grandparents, due to the similar age and because they have already had sexual experiences, giving them confidence to choose such individuals as relevant sources of information.…”
Section: My Mom Is Not Open To Talk About This I've Tried Before Onmentioning
confidence: 96%